Controlling the microstructure and properties of lithium disilicate glass-ceramics by adjusting the content of MgO. Issue 1 (1st January 2023) - Zhang, Haojie; Liu, Jingxiao; Shi, Fei; Zhang, Haoyuan; Yuan, Xinyu; Li, Yi; Li, Tianci; Zhao, Xinran; Wang, Meiyu
Abstract: In order to obtain lithium disilicate glass-ceramics for dental restoration with both high strength and high translucency, lithium disilicate glass-ceramics with different MgO contents were prepared by melt-casting and heat treatment method. The effects of MgO content on the crystallization temperature, microstructure and flexural strength of lithium disilicate glass-ceramics were investigated. The results indicate that Mg 2+ exists in the form of [MgO4 ] in the network of lithium disilicate glass-ceramics when the MgO content is 0.56 mol% (M0.56), which is beneficial to increasing the homogeneity and thermal stability of the glass system, and short rod-like lithium disilicate crystals can be formed after heat treatment at 840°C. Thus, the obtained lithium disilicate glass-ceramics exhibit excellent comprehensive performance, with the flexural strength being 312 ± 23 MPa, and the average transmittance of visible light being 37.3% (d = 1.62 mm). Especially, the glass-ceramic sample shows better translucency than the commercially available products. The research results are of great significance for developing high performance lithium disilicate glass ceramics and promoting its broad application in the field of dental restoration. Graphical abstract: Image 1 Highlights: Lithium disilicate glass-ceramics with high flexural strength and good translucency were prepared. The coordination number of Mg 2+ with oxygen in the glass-ceramic is closely related to the content of MgO. [MgO6 ] is beneficial to crystallization of lithium disilicate and improvement of strength, but is not good for translucency. [MgO4 ] is conducive to improving the uniformity of lithium disilicate glass-ceramic, which is good for translucency.